Assessing the optical properties of the healthy and emmetropic eye with accommodation - Oliveira, Cristina (2013)
The main goal of this study was to investigate the effect of accommodation on eye's optical quality. Wavefront aberrations data of 35 young emmetropic eyes were measured with the L80 Wave+: (1) ocular aberrations were measured with the wavefront sensor, while the subjects fixated at far and near (40 cm), (2) corneal wavefront aberrations were computed from the Placido disk system's data for distance vision conditions and (3) the internal wavefront component of the eye were determined as the difference between ocular and corneal wavefront aberrations. Ocular wavefront aberrations pattern changed with accommodation, particularly due to changes in the primary spherical aberrations towards negative values. Furthermore, the optical quality of the eye and the retinal image quality changes during near vision.